Une lecture scientiste du génie à la fin du XIXe siècle. L’anormalité des personnalités d’exception selon Cesare Lombroso - Rougé, Dominique (Romanica Silesiana)
Cesare Lombroso, an Italian alienist of the late 19th century, regarded geniuses as higher degenerates, influenced as he was by the theory of degeneration that accounted for mental disorder originating from hereditary defects. In this article, I shed new light on his work “Man of Genius”, in which he focuses on the biography of some great writers to explain how their work stems from pathology, while identifying genius with insanity.I aim at demonstrating that, even though Lombroso’s scientist and reductionist theories may appear ludicrous today, they are nonetheless still alive, concealed within some “beuvistic” interpretations of literature. Key words: Genius, insanity, degeneracy, heredity, scientism, classification.